The Effectiveness Administration of Turmino Acid Booking Towards Reducing Dymenorous Pain in Class VII Adolescent at Mts Nurul Jadid, Desa Indrasakti, Kec. Tapung, Kab. Kampar in 2021 - Fransiska Riati Nova Simbolon (International Archives of Medical Sciences and Public Health, 2022)
Data from the World Health Organization (WHO) found that there were 1,769,425 people (90%) women who experienced dysmenorrhea. On average in European csountries, dysmenorrhea occurs in 45-97% of women. With the lowest prevalence in Bulgaria (8.8%) and the highest reaching 94% in Finland. The incidence of menstrual pain (Dysmenorrhea) in the world is very large, on average more than 50% of women in each country experience dysmenorrhea, the prevalence of primary dysmenorrhea in the United States in 2012 at the age of 12-17 years was 59.7%, with 49% mild dysmenorrhea, 37% moderate dysmenorrhea, and 12% severe dysmenorrhea which resulted in 23.6% of sufferers not attending school. This study is a descriptive study, to determine the effectiveness of the benefits of boiling turmeric acid in reducing dysmenorrhea pain in adolescent girls in grade VII at MTs Nurul Jadid, Indrasakti Village, Kec. Tapung Kab. Kampar Prov. Riau in 2021. The approach used in this research is direct research on the processing of tamarind boiling, which type of research measures the effectiveness of the benefits of boiling tamarind turmeric on reducing dysmenorrhea pain. From the results of the initial survey, there were about 50 respondents of seventh grade girls at MTs Nurul Jadid, around 35 respondents had experienced menstruation and 15 respondents had not had menstruation. And from 35 respondents there are about 70% experiencing dysmenorrhea. It was obtained information that many students complained of pain during menstruation, there were even some students who fainted unconscious because they endured the pain they felt, even almost every month they did not enter because of the pain of dysmenorrhea during menstruation. Based on the results of the research before and after the research, there was a decrease in dysmenorrhea pain after giving sour turmeric decoction as much as 77.7%, because sour turmeric is used as an analgesic that can reduce menstrual pain. The results of the analysis obtained p(0.09) < (0.05), it can be concluded that there is a significant difference between the intensity of acid pain before and after the experiment.